PENGARUH FINANCIAL LITERACY, FINANCIAL ATTITUDE DAN KONTROL DIRI TERHADAP PERILAKU MANAJEMEN KEUANGAN MAHASISWA FAKULTAS EKONOMI TAHUN 2021 - ester meyta omega; Edi Wibowo; Dorothea Ririn Indrastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
The purpose analyze the effect of financial literacy, financial attitude and self-control on financial management behavior in students of the Faculty of Economics, Slamet Riyadi University, Surakarta in 2021. The research population is Active Students of the Faculty of Economics, Slamet Riyadi University, Surakarta in 2021. The sampling technique uses the proportional stratified technique. random sampling. Data collection techniques using questionnaires. Analysis of the data used is multiple linear regression analysis, F test, t test and coefficient of determination. The results of this study indicate that Financial Literacy has a significant effect on Financial Management Behavior. Financial Attitude has a significant effect on Financial Management Behavior. Self-control has a significant effect on Financial Management Behavior. The influence given by the independent variables, namely Financial Literacy, Financial Attitude and Self-Control on the related variable, namely Financial Management Behavior, is 99.2% while the rest (100% - 99.2%) = 0.8% is influenced by other factors outside the variables studied.